2022
DOI: 10.1159/000525850
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Assessment in Endometrial Atypical Hyperplasia

Abstract: <b><i>Objective:</i></b> Atypical endometrial hyperplasia (AH) is the neoplastic precursor more often associated with endometrial cancer (EC). Nowadays, 25–50% of patients subjected to hysterectomy for preoperative AH are diagnosed with EC at the final pathological analysis. Furthermore, there is no consensus on which preoperative AH patients would benefit from sentinel lymph node mapping. This study aimed to evaluate nodal assessment and preoperative cancer risk factors in preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…21,22 The literature regarding the performance of SLN biopsy in EIN is limited to retrospective descriptions of relatively small cohorts. 8,10,23 Traditional statistics and machine learning analyses were unable to identify which patients with EIN will have endometrial carcinoma on final pathology, although some retrospective data suggest that endometrial thickness and age are associated with higher risk of endometrial carcinoma. [24][25][26] Although there are recent studies on the uptake and outcomes of SLN biopsy in endometrial carcinoma, 27 these are underreported in EIN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 The literature regarding the performance of SLN biopsy in EIN is limited to retrospective descriptions of relatively small cohorts. 8,10,23 Traditional statistics and machine learning analyses were unable to identify which patients with EIN will have endometrial carcinoma on final pathology, although some retrospective data suggest that endometrial thickness and age are associated with higher risk of endometrial carcinoma. [24][25][26] Although there are recent studies on the uptake and outcomes of SLN biopsy in endometrial carcinoma, 27 these are underreported in EIN.…”
Section: Discussionmentioning
confidence: 99%
“…Of patients with a preoperative diagnosis of EIN and postoperative pathology of endometrial carcinoma, approximately 10% will have high-risk endometrial carcinoma, in which evaluation of the lymph nodes may support the recommendations regarding adjuvant therapy. [8][9][10] It is common for general gynecologists to perform surgery for patients with EIN. A large study identified that 33.2% of hysterectomies with a final diagnosis of EIN were not performed by a gynecologic oncologist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Capozzi et al registered a lymph node positivity of 0.7% (1/54). At the same time, 9.9% (15/152) of patients with AEH received a final diagnosis of endometrial carcinoma at intermediate or higher risk, confirming the elevated number of patients who could obtain information from nodal assessment [ 63 ].…”
Section: Data On Lymph Node Status Assessment In Atypical Endometrial...mentioning
confidence: 97%
“…As shown in Table 6 , the selected articles were all retrospective studies and considered a total of 22,201 women [ 3 , 4 , 43 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. The rate of occult endometrial carcinoma in patients with a preoperative diagnosis of AHE ranged from 27.2 to 53.3%, consistent with the previous literature [ 1 , 2 ].…”
Section: Data On Lymph Node Status Assessment In Atypical Endometrial...mentioning
confidence: 99%